Academic stress and academic performance among early childhood education students in Peru - Alvaro Camposano-Cordova; Juan Antonio Picoy-Gonzales; Néstor Jesús Caro-Seminario; Clorinda Barrionuevo-Torres; José Antonio Nieto-Custodio; Maria Clarisa Tovar-Torres-De-Aguilar; Melina Penélope Tolentino-Cotrina; Nelly Olga Zela-Payi; Jesus Mery Arias-Huanuco; Wendy Nelly Bada-Laura; Rosaura Huarcaya-Taype; Gladys Margarita Espinoza Herrera; Christian Luis Torres-Acevedo; Daniel Joel (Institute of Advanced Engineering and Science, 2026)
Academic stress is widely assumed to impair academic performance in higher education; however, empirical evidence remains inconsistent, particularly in professional teacher-training programs. This study examined the relationship between perceived academic stress and academic performance among 116 undergraduate students (18–25 years) enrolled in an early childhood education program at a public university in Peru. A quantitative cross-sectional correlational design was employed. Academic stress was measured using the perception of academic stress scale, while academic performance was obtained from official grade point averages (GPA), ensuring objective assessment. Data were analyzed using multiple regression and non-parametric tests (Mann–Whitney U and Kruskal–Wallis H). Results indicated moderate stress levels (M=3.65) and stable academic performance (M GPA=14.72). Academic stress did not significantly predict GPA, whereas age emerged as the only significant positive predictor. Gender and academic cycle showed no significant effects. These findings suggest that academic stress may not necessarily undermine performance and highlight the potential role of maturity and adaptive capacities in supporting resilience among future teachers.